Nutritional strategies for laying hens to address environmental challenges by reducing the nitrogen excretion - Vlaicu Petru Alexandru; Untea Arabela Elena; Panaite Tatiana Dumitra; Cornescu Gabriela Maria; Saracila Mihaela; Varzaru Iulia; Oancea Alexandra Gabriela (Food and Feed Research)
This research aimed to assess the impact of incorporating Castanea sativa powder (CSP) into laying hens diets, examining reduced crude protein (CP) levels and their effects on production performance, haematological parameters, nutrients and mineral digestibility and environmental pollution by nitrogen (N) absorption and excretion. For that, a 6-week trial was developed, with 90 Lohmann Brown laying hens aged 51 weeks, raised in digestibility cages, divided into three groups with 30 hens each. The diets were composed as follows: a control group fed with 17.50% crude protein (CON), an experimental group with a reduced CP level of 15.50% (RPL), and a similar reduced CP group supplemented with 0.5% CSP (RPC) as tannin additive. The limiting amino acids (lysine, methionine, and threonine) were supplemented to maintain constant equal amino acid concentrations in all experimental diets. Throughout the feeding trial, the laying rate was higher in the RPC group (94.12%), followed by RLP (93.65%) and CON (91.11%). However, CON hens produced heavier eggs compared to RPL and RPC groups. Average daily feed intake and feed conversion ratio showed no significant differences (p>0.05) between the groups. Results from blood samples showed a significant increase (p<0.05) in RPL group on monocytes and uric acid compared with CON and RPC groups with tendencies for leucocytes, lymphocytes, heterophiles. Notably, excreted N levels were significantly reduced (up to 30%) in RPL (0.33 mg N/100g) and RPC (0.30 mg N/100g) groups compared to the CON (0.42 mg N/100g) group, showing a promising way of reducing N pollution. The RPC group had significantly higher (p<0.05) N content and coefficient of apparent N absorption compared with RPL group. On the other hand, the CP excretion was significantly lower (p<0.05) in the RPL (2.06 mg CP/100g) and RPC (1.94 mg CP/100g) groups compared with CON group (2.63 mg CP/100g). The lowest CP absorption was determined in the RPL group, while the RPC group (88.24%), had the highest coefficient of apparent absorption, compared with both CON (86.18%) and RPL (86.22%) groups. No significant effect on mineral excretion content was observed.